PENINGKATAN KETERAMPILAN PENYUSUN PARAGRAF KARANGAN DESKRIPSI MENGGUNAKAN MODEL PICTURE AND PICTURE DI SEKOLAH DASAR - Sari, Fitri; kresnadi, Hery; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve the ability of teachers in planning, implementing learning and student learning outcomes in preparing paragraphs essay description using the model picture and picture class 3B elemntary school 36 pontianak selatan. The method used is desricptive with the form of classroom action research and collaborative. The subjects of this study werw teachers and students of grade 3 B, amouting to 25 students, this study was conducted in grade 3B public elementary school 36 pontianak selatan. The procedures used there are 4 stages of planning, implementation, observation, and reflection. Technique in this research is abservation and careful document. Planning, execution and writing skill are analyzed using the average formula. The study was conducted in 2 cycles with 2 meetings in each cycle. Assessment of learning outcomes in cycle 25 completed students ie 32% ( 8 students) while the unifinished 68% (17 students) with an average score of 65,74. Experienced an increase cycle of 25 completed students of 64% (16 students) wkile 36% (9 students) complete with an average score of 73,77. Thus, research using picture and picture model can improve skill of arrange paragraph essay description of student grade 3B elemntary school 36 pontianak selatan. Keywords: Essay Description, Picutre and picture Model and Image.